The Grateful Don't Cheat: Gratitude as a Fount of Virtue. (July 2019) - DeSteno, David; Duong, Fred; Lim, Daniel; Kates, Shanyu
Gratitude has been linked to behaviors involving the exchange of resources; it motivates people to repay debts to benefactors. However, given its links to self-control—itself a necessary factor for repaying debts—the possibility arises that gratitude might enhance other virtues unrelated to exchange that depend on an ability to resist temptation. Here, we examined gratitude's ability to function as a "parent" virtue by focusing on its ability to reduce cheating. Using real-time behavior-based measures of cheating, we demonstrated that gratitude, as opposed to neutrality and the more general positive emotional state of happiness, reduces cheating in both a controlled laboratory setting ( N = 156) and a more anonymous online setting ( N = 141). This finding suggests that not all moral qualities need to be studied in silos but, rather, that hierarchies exist wherein certain virtues might give rise to seemingly unrelated others.